Loss of KATP Channel Activity in Mouse FDB Leads to an Impairment in Energy Metabolism During Fatigue - Scott, Kyle (Université d'Ottawa / University of Ottawa, 2012)
Recently, it has been postulated that fatigue is a mechanism to protect the muscle fiber from deleterious ATP depletion and cell death. The ATP-sensitive potassium (KATP) channel is believed to play a major role in this mechanism. Under metabolic stress, the channels open, reducing membrane excitability, Ca2+ release and force production. This alleviates energy demand within the fiber, as activation of the channel reduces ATP consumption from cellular ATPases. Loss of KATP channel activity during fatigue results in excessive intracellular Ca2+ ([Ca2+]i) levels, likely entering the fiber through L-type Ca2+ channels. It has been demonstrated that when mouse muscle lacking functional KATP channels are stimulated to fatigue, ATP levels become significantly lower than wild type levels. Thus, it was hypothesized that a lack of KATP channel activity impairs energy metabolism, resulting in insufficient ATP production. The focus of work for this M.Sc. project was to test this hypothesis. Fatigue was elicited in Kir6.2-/- FDB muscles for three min followed by 15 min recovery. After 60 sec, a 2.6-fold greater glycogen breakdown was observed in Kir6.2-/- FDB compared to wild type FDB. However, this effect disappeared thereafter, as there were no longer any differences between wild type and Kir6.2-/- FDB in glycogen breakdown by 180 sec. Glucose oxidation after 60 sec was also greater in Kir6.2-/- FDB compared to wild type FDB. However, levels of oxidation failed to increase in Kir6.2-/- FDB from 60 to 180 sec. Calculated ATP production during the fatigue period was 2.7-times greater in Kir6.2-/- FDB, yet measured ATP levels during fatigue are much lower in Kir6.2-/- FDB compared to wild type FDB. Taken together, it appears that muscle energy metabolism is impaired in the absence KATP channel activity.
Keywords: skeletal muscle fatigue; KATP channel; metabolism